(untitled) (Medical Forum Monthly, 2023)
Objective: This study aims to determine the role of the novel drug vonoprazan base dual therapy in high doses for HP eradication in the Pakistani population. Study Design: Descriptive-cohort study Place and Duration of Study: This study was conducted at the Ethical Board Khushal Medical Center Peshawar from September 2022 to February 2023. Methods: This descriptive cohort study includes 102 HP positive treatment naïve patients. All the patients were given vonoprazan 40mg OD and amoxicillin 1gm BD for 10 days. All the patients were followed for 3 weeks and then re-evaluated. The data were recorded on predesigned proforma and all the data were analyzed using SPSS version 22.0. Results: In 102 participants, the mean age was 50.2±3.2 years while distribution of males to females was 36.3 and 63.7% respectively. Vonoprazan-based treatment completely eradicated H.P in 84.3% of patients while 15.7% of patients were non-responders. Gender and age does not influence the treatment outcome of the patients (p values >0.05). Conclusion: High dose vonoprazan plus amoxicillin might be superior to other treatment regimens in the eradication of HP infections particularly in our vicinity.